Evaluation of Adansonia Digitata (Baobab) Leaf and Root Extracts as Inhibitor on Dual Phase Steel (DPS) in 0.3M H2SO4 - Dongo , E Isaac; Momoh , I Monday; Banabars , A Abel (American Journal of Computing and Engineering, 2022)
Purpose: In this work, the effect of indigenously sourced baobab leaf and root was experimented on the substrate of inter-critically developed dual phase steel in 0.3M H2SO4. Methodology: Standard techniques were adopted in carrying out the development and the corrosion experiments. Weight loss method was adopted and the corrosion rate eventually estimated following a standard route. Findings: From the results, it was observed that inter-critical heat treatment technique can be used to develop dual phase steel with a competing properties with the conventional dual phase steel. The use of baobab leaf and root extracts was also observed to serve as an organic inhibitor for dual phase steel having observed that the percentage inhibition efficiency (% IE) increases with increase in the soaking temperature of the developed DPS. Recommendation: The use of baobab leaf and root is thus recommended as alternative organic inhibitor to impede corrosion rate in DPS.